Efforts to Prevent Stunting by Enhancing Cadres Knowledge and Attitudes on Infant and Young Child Feeding - Ari Indra Susanti; Putri Argi Larasati; Tisnasari Hafsah; Dida Akhmad Gurnida (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2025)
Stunting is a global health issue that affects physical growth, cognitive development, and future productivity. WHO (2022) reported that 22.3% of children under five years old experience stunting worldwide, with a prevalence of 26.4% in Southeast Asia. In Indonesia, the stunting prevalence is 21.7%, while in Bandung City, it reaches 16.3% (Kemenkes, 2023). One of the efforts to prevent stunting is educating community health cadres on Infant and IYCF as agents of change in society. This study employed a descriptive method with a cross-sectional approach involving 400 community health cadres in Bandung City. The training was conducted using a blended learning approach, combining online and offline sessions over four stages. Evaluation was performed through pretest and posttest assessments to measure knowledge improvement and attitude changes among cadres. The results showed an increase in cadre knowledge from 49.7% before the training to 67.8% after the training. However, negative attitudes toward IYCF increased from 46.2% to 56.4%, likely due to implementation challenges in the field. These findings highlight that while training effectively enhances cadre knowledge, practical application in communities still faces obstacles. Therefore, policy support, cross-sectoral involvement, and more effective communication strategies are needed to enable cadres to optimize their role in stunting prevention.